Pattern of Risk Factors Associated with Pregnancy among the Recently Delivered Women (Anwer Khan Modern Medical College Journal, 2020)
Background: ‘Pregnancy risk’ is defined as the probability of dying or experiencing severe injury as theresult of pregnancy or childbirth. High maternal mortality rate can be decreased by reduction of pregnancy risk among the women.Objectives: To find out the pattern of pregnancy risk among the recently delivered women.Methods and Material: This cross sectional study was conducted in gynecology and obstetrics department of Dhaka Medical College, Hospital and Combined Military Hospital, Dhaka from January 2004 to July 2004. Semi structured questionnaire was used as data collection instrument. Collected data were analyzed by SPSS.Results: A total number of 124 recently delivered women were studied during this period. The study revealed that most of the respondent 36.3% were 20-24 years of age groups. Most of the respondents 90.3% were housewife, 24.2% were illiterate and 91.1 % received antenatal care. About 31.5% had previous bad obstetric history and 25.8% had morbidity during pregnancy. The frequent compliant was high blood pressure in 37.5%. Among the respondents 45.2% had obstetric problem during recent pregnancy and highest percentage had complaint of dependent oedema is 51.8%. About 60.5% respondents faced problem during delivery and 12.9% had history of complication after delivery. The study revealed that 62.5% of age group _ 35 had 3 risk factors compared to 26.9% of age group 20-35 had 3 risk factors. The proportion of 3 risk factors were higher among the mothers whose husband were day labour (59.1%) compared to service holder (26.3%) and businessman (22.7%). The proportion of >_ 3 risk factors were higher among the mother with history of two abortion (85.7%) as compared to single abortion (51.7%) and no abortion (20.5%). The study revealed that pregnancy risk was statistically significant in relation to age, occupation, education, number of pregnancy and number of abortion among the recently delivered women.Conclusion: The result of this study would be helpful in making appropriate interventions for pregnancy risk factors reduction in terms of proper anti natal care, safe delivery system and post-natal care.AKMMC J 2020; 11(2) : 91-96